2022
DOI: 10.48550/arxiv.2207.09026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Universality and Critical Exponents of the Fermion Sign Problem

Abstract: Initial characterizations of the fermion sign problem focused on its evolution with spatial lattice size L and inverse temperature β, emphasizing the implications of the exponential nature of the decay of the average sign S for the complexity of its solution and associated limitations of quantum Monte Carlo studies of strongly correlated materials. Early interest was also on the evolution of S with density ρ, either because commensurate filling is often associated with special symmetries for which the sign pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…It has been recently demonstrated that the average sign of the weights extracted over the course of the importance sampling in quantum Monte Carlo simulations of various fermionic models can be used to both qualitatively [5] and quantitatively [6] identify the loci of quantum critical points. Here, we show that this analysis does not in principle hold in the case of the Hubbard model in the triangular lattice, both on its U(1) or SU(2) formulations, at least using the 'standard' Hubbard-Stratonovich transformation described in the Appendix A.…”
Section: Appendix G: the Sign Problem In Non-bipartite Geometriesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently demonstrated that the average sign of the weights extracted over the course of the importance sampling in quantum Monte Carlo simulations of various fermionic models can be used to both qualitatively [5] and quantitatively [6] identify the loci of quantum critical points. Here, we show that this analysis does not in principle hold in the case of the Hubbard model in the triangular lattice, both on its U(1) or SU(2) formulations, at least using the 'standard' Hubbard-Stratonovich transformation described in the Appendix A.…”
Section: Appendix G: the Sign Problem In Non-bipartite Geometriesmentioning
confidence: 99%
“…While recent studies have in fact suggested that the average sign of weights in the latter already pinpoints the regimes of strong quantum fluctuations [4][5][6][7], here we focus on other statistical properties that also aid in locating quantum phase transitions. In particular, we investigate a specific class of QMC methods for ddimensional fermionic systems, referred to as auxiliary field QMC [2,8,9], which provides a framework to stochastically average observables by sampling a fictitious field in d + 1-dimensions, introduced in a path integral formulation of the partition function.…”
Section: Introductionmentioning
confidence: 99%
“…Or more strictly speaking, those positive examples where the average sign can probe the critical value can be excep- tional cases. On the other hand, in previous studies, the phase transition can be related to the sign value itself or its derivative in different circumstances without an explicit criterion [32][33][34][35][36][37][38]. This non-conformity has also been discussed in the present work.…”
mentioning
confidence: 66%
“…Therefore, the formation of permutation cycles [43], which are exclusively responsible for a non-unity sign in standard PIMC, is suppressed, which explains the observed trend. While the average sign by itself does not constitute a physical observable, it can nevertheless give insights into the physical behaviour of a given system in some situations [146,147]. In the top panel of Fig.…”
Section: Effect Of the Densitymentioning
confidence: 99%